KUALITAS INFORMASI LAPORAN KEUANGAN ENTITAS SEKTOR PUBLIK DAERAH X - Marsdenia Marsdenia (Program Pendidikan Vokasi Universitas Indonesia, 2016)
This study has objective to analyze factors influencing public sector entity’s financial statement informationsquality. Factors examined include quality of human resources, internal control system, information technologyutilization and external factors as a moderating variable. Originally RSUD X is Private Hospital namelyRS Y Kota A, then, in Mid 2014 have been transformed to be RSUD X as local gorvernment hospital City ofA. Metodologi research for this study is Quantitative Research Method by Questionnaires or Surveys approachthrough respondent for this study is the human resources involved in the functions of accounting, finance andBilling for BPJS and staff who handle in patient account. Respondent in RSUD Bogor totally 42 staffs. TheData collected from questionnaires analyzed by multiple linear regression methods. The Result show thatKeyword; content, formatting, article.Local Government Hospital, Financial Statement, Quality of information, Public Sector’s Entity.